Community Health Workers and Social Proximity: Implementation of a Parenting Program in Urban Poverty. Issue 3 (17th September 2018) - Gustafson, Erika L.; Atkins, Marc; Rusch, Dana
Abstract: Community health workers (CHWs) offer a potential means through which to mitigate many of the barriers to mental health services faced by minority youth and their families. The primary aim of the present study was to better understand a core feature of CHWs: their shared community membership with the population served, or social proximity . We conducted qualitative semi‐structured interviews with 16 CHWs implementing a school‐based early intervention program in Latino and African American communities of urban poverty. The program promoted child and parent/caregiver engagement in schooling as a protective factor for children's mental health. Thematic analyses revealed three main themes defining social proximity: (a) experiences of parenthood or caring for children, (b) familiarity with and understanding of culture, and (c) experiences of life hardships and struggles. Additionally, the process of relating with parents/caregivers through shared experiences was the main theme to describe how CHWs leveraged their social proximity. CHWs' accounts illustrated how their experience of social proximity to the population served was central to how they engaged parents/caregivers in services, highlighting the importance of supporting and promoting CHWs' natural traits and lived experiences. Highlights: CHWs defined their social proximity through shared experiences of parenthood, culture, and hardships. The process of relating was central to how CHWs engaged the population served. CHWs' natural traits and lived experiences are defining features of their role. CHWs' natural traits and lived experiences are also what CHWs draw upon to promote service engagement.